Pre-Clustering of the B Cell Antigen Receptor Demonstrated by Mathematically Extended Electron Microscopy - Fiala, Gina J.; Kaschek, Daniel; Blumenthal, Britta; Reth, Michael; Timmer, Jens; Schamel, Wolfgang W. (Frontiers in Immunology, 2013)
The B cell antigen receptor (BCR) plays a crucial role in adaptive immunity, since antigen-induced signalling by the BCR leads to the activation of the B cell and production of antibodies during an immune response. However, the spatial nano-scale organization of the BCR on the cell surface prior to antigen encounter is still controversial. Here, we fixed murine B cells, stained the BCRs on the cell surface with immuno-gold and visualized the distribution of the gold particles by transmission electron microscopy. Approximately 30% of the gold particles were clustered. However the low staining efficiency of 15% precluded a quantitative conclusion concerning the oligomerization state of the BCRs. To overcome this limitation, we used Monte Carlo simulations to include or to exclude possible distributions of the BCRs. Our combined experimental-modelling approach assuming the lowest number of different BCR sizes to explain the observed gold distribution suggests that 40% of the surface IgD-BCR was present in dimers and 60% formed large laminar clusters of about 18 receptors. In contrast, a transmembrane mutant of the mIgD molecule only formed IgD-BCR dimers. Our approach complements high resolution fluorescence imaging and clearly demonstrates the existence of pre-formed BCR clusters on resting B cells, questioning the classical cross-linking model of BCR activation.